2009
DOI: 10.1124/dmd.108.024109
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, Metabolism, and Excretion of Darunavir, a New Protease Inhibitor, Administered Alone and with Low-Dose Ritonavir in Healthy Subjects

Abstract: ABSTRACT:Absorption, metabolism, and excretion of darunavir, an inhibitor of human immunodeficiency virus protease, was studied in eight healthy male subjects after a single oral dose of 400 mg of [ 14 C]-darunavir given alone (unboosted subjects) or with ritonavir [100 mg b.i.d. 2 days before and 7 days after darunavir administration (boosted subjects)]. Plasma exposure to darunavir was 11-fold higher in boosted subjects. Total recoveries of radioactivity in urine and feces were 93.9 and 93.5% of administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 12 publications
2
64
0
Order By: Relevance
“…The unbound fraction of drug is considered the only effective fraction available for the diffusion or penetration into tissues. The darunavir plasma free fraction was 7.2% (5.9 to 9.0%) and was consistent with 95% protein binding primarily to plasma alpha 1-acid glycoprotein (21). There was a good correlation between darunavir total and free fractions of plasma proteins (r 2 ϭ 0.827; P Ͻ 0.0001).…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…The unbound fraction of drug is considered the only effective fraction available for the diffusion or penetration into tissues. The darunavir plasma free fraction was 7.2% (5.9 to 9.0%) and was consistent with 95% protein binding primarily to plasma alpha 1-acid glycoprotein (21). There was a good correlation between darunavir total and free fractions of plasma proteins (r 2 ϭ 0.827; P Ͻ 0.0001).…”
mentioning
confidence: 54%
“…Darunavir-ritonavir is an appropriate candidate for protease inhibitor (PI) monotherapy in maintenance therapy due to its high genetic barrier (5), high potency on naive and resistant HIV strains (11,15), and good pharmacokinetics profile (21). MONOI is an ongoing, 96-week, multicenter, randomized, open-label trial with a primary endpoint at week 48 (W48).…”
mentioning
confidence: 99%
“…Combined with our data obtained in the present study, these clinical findings support inhibition of presystemic LPV metabolism in human small intestine as a major mechanism underlying the pharmacokinetic boosting of LPV by RTV. In contrast to the 10-fold increase in LPV C max , RTV boosting resulted in a C max increase of only 49 to 77% for IDV (Hill et al, 2009) and 88% for DRV (Vermeir et al, 2009). This increase is lower, than would be expected based on our results obtained in the in situ perfusion experiments, suggesting that data obtained in mice regarding the effect of P-gp inhibition might somewhat overpredict the situation in humans.…”
Section: Discussionmentioning
confidence: 80%
“…Among the HIV PI that have been approved, lopinavir, atazanavir, darunavir and fosamprenavir are most frequently prescribed. 5,6 HIV PI are extensively metabolized by CYP3A enzymes 7,8 and their biliary excretion is mediated by the efflux transporters P-gp (ABCB1) and MRP2 (ABCC2). 8,9 In addition, it has been shown that some HIV PI (or their metabolites) are excreted via the feces for more than 75 %.…”
Section: Introductionmentioning
confidence: 99%